Synthesis and characterization of Substituted Carbazole Diphenyl Stilbenes - Chernenko, Daria (Univerzita Pardubice, 2022)
This diploma thesis deals with the synthesis and characterization of carbazole stilbene derivatives, which were not previously described in the literature. Carbazole stilbene derivatives have found application in biomodeling and OLED technologies, that is why they are of such scientific interest today. In the theoretical part, carbazole stilbenes were described as fluorescent compounds, and their spectral behavior was presented, based on scientific research. The experimental part was devoted to the methods and techniques for the synthesis of the molecules proposed in the theoretical part, the choice of the best method, the description of the results and, finally, the characterization of the molecules with available methods.
Syntéza a charakterizace substituovaných karbazol difenyl stilbenů
Keywords: chromofor; karbazol; stilben; D-pí-A; Horner-Wadsworth-Emmonsova reakce; fluorescence; chromophore; carbazole; stilbene; D-pí-A; Horner-Wadsworth-Emmons reaction; fluorescence